2013
DOI: 10.3928/00220124-20130315-81
|View full text |Cite
|
Sign up to set email alerts
|

Preceptors’ Perceptions of Their Role in a Pediatric Acute Care Setting

Abstract: Preceptors perceived sufficient benefits and rewards to remain committed to the role and identified workload as a significant challenge. Further research is needed to explore whether additional supports or recognition tailored to level of experience and age may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
(42 reference statements)
4
4
0
Order By: Relevance
“…The success of the preceptorship program depends very much on the commitment of preceptors to their role [ 15 ]. In this study, the preceptors rated their commitment to the preceptor role as moderate, which is consistent with previous international research [ 15 , 19 , 21 , 22 , 24 ]. These findings indicate the need for a better understanding of the preceptors’ viewpoints, experience, and perceived barriers and facilitators to help meet their needs and enhance their commitment to the role.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The success of the preceptorship program depends very much on the commitment of preceptors to their role [ 15 ]. In this study, the preceptors rated their commitment to the preceptor role as moderate, which is consistent with previous international research [ 15 , 19 , 21 , 22 , 24 ]. These findings indicate the need for a better understanding of the preceptors’ viewpoints, experience, and perceived barriers and facilitators to help meet their needs and enhance their commitment to the role.…”
Section: Discussionsupporting
confidence: 90%
“…The scores for these items were reversed when analyzing the responses. The validity and reliability of the questionnaire have been established internationally [ 21 , 22 ]. In the original study, Cronbach’s Alpha coefficients for the three scales of the PPBR, the PPS, and the CPR were reported as 0.91, 0.86, and 0.87, respectively [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Participants felt proud and honored of being chosen as a preceptor. This feeling is an experience which indicates participants' commitment to preceptorship and commitment to one's own continual growth (Chang et al, 2013;Watson et al, 2012). Moreover, they thought of their selection as endorsement of their skills and this had reinforced their selfconfidence.…”
Section: Empathymentioning
confidence: 93%
“…Our current understanding of the experience of precepting has developed from several studies of experienced nurses from various clinical environments, predominantly chronic and low acuity settings. Our understandings of preceptors from high acuity environments is limited to a single study within a paediatric critical care environment (Chang et al 2013). In this study, age and experience were identified as factors that lead to preceptors reporting different rewards.…”
Section: Introductionmentioning
confidence: 96%
“…Rewards included: preceptor satisfaction; selfdevelopment and promotion; helping students apply knowledge to practice; and preparation for leadership positions (Liu et al 2010, Hyrkas & Shoemaker 2007. Experienced nurses with educational preparation have reported both a greater number of rewards and higher commitment scores to the preceptor role compared to nurses without educational preparation (DeWolfe et al 2010, Chang et al 2013. Furthermore, diminished commitment to precepting undergraduate students has been shown to result from perceived lack of reward M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 (Kalischuk et al 2013).…”
Section: Introductionmentioning
confidence: 99%